Common Diseases in Early Childhood and Their Prevention Strategies: A Posyandu-Based Observational Study In Parepare City - Hardiana; Asmita; Suarna; Rosita; Canni; Nurdiana; Janu Lena Geken; Nurinaya Suleman; Maswati (CV Edujavare Publishing, 2026)
Background: Early childhood (0–6 years) represents the most vulnerable population for infectious diseases due to an incompletely developed immune system. The high incidence of diseases such as acute respiratory infections (ARI), diarrhea, fever, chickenpox, and skin diseases constitutes a significant public health problem in Indonesia, including in Parepare City, South Sulawesi. The role of integrated health posts (posyandu) as the frontline of primary healthcare services is crucial in monitoring the health status of early childhood. Objective: This study aimed to identify the most common diseases in early childhood, analyze their risk factors, and describe prevention strategies implemented at posyandu. Methods: This study employed a posyandu-based descriptive observational design using a mixed-method concurrent triangulation approach. Quantitative data were obtained through direct observation of Posyandu Damai activities on April 11, 2026 and review of visit records from January to April 2026, while qualitative data were collected through semi-structured interviews with posyandu cadres, a community health center midwife, and attending parents or guardians. The units of analysis included 93 registered children, 65 children attending the observation session, and 87 disease-case records documented in the visit recapitulation. Data were analyzed using descriptive statistics to calculate frequencies and percentages, and thematic analysis to interpret risk factors and prevention strategies. Results: Findings indicated that 65 of 93 registered children attended the observation session, while the health-status recapitulation showed that 88 children were healthy and 5 experienced health problems. The most frequently encountered diseases included fever (32.4%), cough and common cold/ARI (28.7%), diarrhea (18.5%), intestinal worms (12.1%), and allergies (8.3%). Key risk factors identified were nutritional imbalances, poor environmental sanitation, inadequate handwashing habits, and low parental knowledge about balanced nutrition. Prevention strategies implemented by posyandu include nutritional counseling, vitamin and supplement distribution, immunization, and Clean and Healthy Living Behavior (PHBS) education. Conclusion: Posyandu plays a strategically vital role in improving the health status of early childhood. Synergy among posyandu cadres, healthcare workers, and parents is the key to successful disease prevention in early childhood. Enhanced community-based education programs and promotional-preventive approaches need to be continuously strengthened to reduce disease incidence in children